EFFECTS OF TEMPERATURE FIELD AND ABNOMAL VARIATIONS OF SEA WATER LEVEL IN EAST VIETNAM SEA IN RELATIONSHIP TO GLOBAL CLIMATE CHANGE - Chung, Tran Van; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2016)
During 2010, the sea water level in East Vietnam Sea has been raised with an extremely high amplitude as many foreign authors recorded recently that was derived from the analysis of multi temporal (1993 - 2010) satellite altimeter data series. This is one of anomalous changes of nature that was strongly relative to climate change. In another aspect, by using the combination of temporal-spatial changes of the air temperature, sea surface temperature as well as seawater level, authors will try to explain more clearly this above interesting phenomenon that happened in East Vietnam Sea. The used data series in this study were obtained from reanalysis data of CFSR-NCEP with time step of 1 hour and spatial resolution of 0.3150, and data series of sea  water level was derived from HYCOM+NCODA with grid size of 1/12.50. The analyzed results explained more clearly the strong relationship of climate change with temporal change of the air and the sea water temperatures as well as sea level rise in the area of East Vietnam Sea.